Optimalisasi Manajemen Laboratorium Guna Meningkatkan Mutu Pembelajaran Fisika di Berbagai Jenjang Pendidikan - Muhammad Wildan Afifi; Rika Dwi Susanti; Aqilla Mumtaza; Desyana Olenka Margaretta (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Effective laboratory management is an important element in order to improve the quality of learning, especially in physics. This research is motivated by the need for a structured laboratory management system to ensure efficiency, safety, and sustainability of practicum activities. The purpose of this study was to examine the implementation of laboratory management at various levels of education as a real step in an effort to improve the quality of physics learning. The method used is descriptive qualitative, with data collection through literature study. The results showed that the implementation of laboratory management which includes aspects of planning, organizing, implementing, and evaluating has improved the quality of physics learning itself. Apart from the various supporting and inhibiting factors in it.